Functional dissection of phytochrome A in plants - Lei, Yuqi; Ma, Qi; Zhang, Yihao; Li, Jilian; Ning, Xinzhu; Wang, Yichen; Ge, Xiaoyang; Zhao, Hang; Lin, Hai (Frontiers in Plant Science, 2024)
Plants lack behavioral responses to avoid dramatic environmental changes associated with the annual seasons. For survival, they have evolved complex sensory systems to sense fluctuations in light and optimize their architecture in response to changes in these cues. Phytochrome A (phyA) was initially identified as a photoreceptor that senses far-red light signals. It was then identified as playing a central role in promoting hypocotyl growth, fiber development, and flowering time in a variety of plants including Arabidopsis, rice, soybean and cotton. Under dark conditions, phyA is present in the cytoplasm in the physiologically inactive (Pr) form. Far-red light signals induce the transformation of Pr into the physiologically active (Pfr) (physiologically inactive) form, after which Pfr-phyA is recognized by FAR-RED ELONGATED HYPOCOTYL 1 (FHY1) and FHY1-LIKE (FHL) and translocated to the nucleus, initiating a series of signaling cascades. The current review comprehensively summarizes recent advances in understanding the function of phyA in plants, including phyA-mediated shade avoidance and flowering time. Remaining issues and possible directions for future research on phyA are also discussed.